Analisis Pengendalian Internal dalam Perencanaan Aset Barang Milik Negara oleh Kantor Pusat DJBC - Nur Fadirah, Amanda; Utaminingtyas, Tri Hesti; Khairunnisa, Hera (LPPM Universitas Negeri Jakarta, 2025)
This study aims to analyze internal control in planning the inventory needs of State Property (BMN) assets in 2024 based on the Government Internal Control Standards (SPIP). In addition, this study provides recommendations for a pocketbook on internal control in planning the needs of BMN inventory assets to overcome gaps in internal control over planning the needs of BMN inventory assets. This study uses the Head Office of the Directorate General of Customs and Excise (DJBC) as the research object. This type of research is qualitative with a descriptive analysis approach. The data sources used come from primary data and secondary data. Primary data is in the form of interviews while secondary data is in the form of documentation on planning the needs of BMN inventory assets. The results of this study indicate that internal control in planning the needs of BMN inventory assets has been running by the technical instructions for planning the needs of BMN inventory assets, but there are still several internal control principles that are not under the principles of SPIP.